Formulasi Prioritas Program Corporate Social Responsibility di Bank Syariah: Perspektif Maqasid Al-Shariah - Prasetiyo, Luhur (UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
Introduction: This study aims to formulate a priority framework for CSR programs in Islamic banks. The formulation can be used to remove the stigma that Islamic banks' CSR motives are only for economic and corporate interests. Research Methods: This qualitative study formulated a priority framework for CSR programs in Islamic banks using the maqasid al-shariah approach. This type of research was literature research. As a sample, researchers determined two Islamic banks in Indonesia: Bank Muamalat and Bank Syariah Indonesia. The two banks represent the oldest and largest banks in Indonesia. The data was analyzed using content analysis methods and critical study methods. Results: Islamic bank CSR is implemented in the social, economic, educational, and health sectors. The priority of Islamic bank CSR activity programs is based on maqasid al-shariah in accordance with their respective elements and levels. Conclusion: Islamic banks can run CSR programs according to their priorities and urgency based on maqasid al-shari'ah. This priority framework for Islamic banks' CSR activities can increase public trust and a positive image of Islamic banks. Islamic banks can eliminate the negative stigma that Islamic banks' CSR is only carried out with the motive of economic and corporate interests alone.